2022
DOI: 10.1038/s41598-022-12228-y
|View full text |Cite
|
Sign up to set email alerts
|

Using population-based data to evaluate the impact of adherence to endocrine therapy on survival in breast cancer through the web-application BreCanSurvPred

Abstract: We show how the use and interpretation of population-based cancer survival indicators can help oncologists talk with breast cancer (BC) patients about the relationship between their prognosis and their adherence to endocrine therapy (ET). The study population comprised a population-based cohort of estrogen receptor positive BC patients (N = 1268) diagnosed in Girona and Tarragona (Northeastern Spain) and classified according to HER2 status (+ / −), stage at diagnosis (I/II/III) and five-year cumulative adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
0
12
0
3
Order By: Relevance
“…The prognosis of HR + BC is declining without AET, no matter if the patient did not start the AET or stopped the AET prematurely. Furthermore, it has been shown that a highly irregular therapy intake has a negative impact on the outcome 32 . This study focused on the initial step in the process of medication intake, that is, the acceptance of AET treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of HR + BC is declining without AET, no matter if the patient did not start the AET or stopped the AET prematurely. Furthermore, it has been shown that a highly irregular therapy intake has a negative impact on the outcome 32 . This study focused on the initial step in the process of medication intake, that is, the acceptance of AET treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that a highly irregular therapy intake has a negative impact on the outcome. 32 This study focused on the initial step in the process of medication intake, that is, the acceptance of AET treatment.…”
Section: Patient Recruitment and Study Settingmentioning
confidence: 99%
“…Etwa 70% aller neu diagnostizierten Frauen mit BK haben einen hormonrezeptorpositiven Tumor (HR +), bei denen eine primäre adjuvante endokrine Therapie (ET) entweder mit Tamoxifen (TAM) oder einem Aromataseinhibitor (AI) in Frage kommt (Franzoi et al, 2021). Diese Standardtherapie wird je nach Menopausenstatus für mindestens 5 Jahre täglich genommen, reduziert das BK-Rezidiv-Risiko signifikant und verbessert das Gesamtüberleben der Patientinnen (Waks & Winer, 2019, Font et al, 2022. Trotz der nachgewiesenen Wirksamkeit der Verhinderung eines BK-Rezidivs um 40% nehmen etwa 50% der Frauen weniger als 80% der verordneten Dosis ein.…”
Section: Discussionunclassified
“…Die Persistenz wird hierbei als die Fortsetzung der Medikamenteneinnahme über den vorgeschriebenen Zeitraum (vom Beginn bis zum Absetzen) definiert, in dem sich eine Patientin an das vorgeschriebene Intervall und die Dosis eines Dosierungsschemas hält (Cramer et al, 2008;Hadji et al, 2013). In jüngster Zeit wurden die Therapietreue und die Persistenz der ET bei Frauen mit HR+ BK in der Literatur intensiv diskutiert, da die "Nicht-Treue" zur ET nachweislich mit einem erhöhten Risiko für ein Krankheitsrezidiv (Font et al, 2019;Seneviratne et al, 2015), für Fernmetastasen (Blanchette et al, 2020;Lee et al, 2019) und für Mortalität (Inotai et al, 2021;Lao et al, 2019;Murphy et al, 2015) verbunden ist. >> Die vorliegende retrospektive Kohortenstudie basierte auf der IQ-VIA-LRx-Datenbank (Richter et al, 2015).…”
Section: Discussionunclassified
“…Once it has occurred under TAM treatment, BC recurrence is usually more aggressive and TAM-resistant than the primary tumor, and discontinuation may thus also be due to increased mortality (due to study limitations, death is also considered a therapy discontinuation) (Font et al 2022;Yan et al 2020). It is important to note that if patients switched ET from TAM to AI (or vice versa) within 180 days after the discontinuation of each therapy, they continued to be considered persistent.…”
Section: Factors Associated With Non-persistencementioning
confidence: 99%